2012
DOI: 10.2458/azu_js_rc.v54i1.15828
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dates from Jar and Coffin Burials of the Cardamom Mountains Reveal a Unique Mortuary Ritual in Cambodia's Late- to Post-Angkor Period (15th–17th Centuries AD)

Abstract: ABSTRACT. We present the first radiocarbon dates from previously unrecorded, secondary burials in the Cardamom Mountains, Cambodia. The mortuary ritual incorporates nautical tradeware ceramic jars and log coffins fashioned from locally harvested trees as burial containers, which were set out on exposed rock ledges at 10 sites in the eastern Cardamom Massif. The suite of 28 14 C ages from 4 of these sites (Khnorng Sroal, Phnom Pel, Damnak Samdech, and Khnang Tathan) provides the first estimation of the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…Our presentation here of the dating and Bayesian treatment of the 14 C results from KPP represents the most extensive data set on the Jar and Coffin Burial ritual thus far assembled by the "Living in the Shadow of Angkor" project, which aims to build an understanding of a highland people who were previously only shadows in the Cambodian archaeological record. As well as extending the chronological record of the Cardamom sites first presented in Beavan et al (2012a), we present some newly observed features for the Jar and Coffin mortuary ritual, including human burials within Angkorian jars, animal remains accompanying some human burials, and evidence of a cultural practice of dental ablation. These discoveries provide new insights about the values and beliefs of this Highland culture.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our presentation here of the dating and Bayesian treatment of the 14 C results from KPP represents the most extensive data set on the Jar and Coffin Burial ritual thus far assembled by the "Living in the Shadow of Angkor" project, which aims to build an understanding of a highland people who were previously only shadows in the Cambodian archaeological record. As well as extending the chronological record of the Cardamom sites first presented in Beavan et al (2012a), we present some newly observed features for the Jar and Coffin mortuary ritual, including human burials within Angkorian jars, animal remains accompanying some human burials, and evidence of a cultural practice of dental ablation. These discoveries provide new insights about the values and beliefs of this Highland culture.…”
Section: Discussionmentioning
confidence: 99%
“…In Beavan et al (2012a), the collection of 12 coffins fashioned from whole logs at Phnom Pel had well-defined growth-ring structures and minimal carving away of outer layers. For the Phnom Pel coffin collection, it was assumed that the outermost ring layer likely represented sapwood suitable for 14 C dating of the time of tree harvest for coffin construction.…”
Section: Coffin Burialsmentioning
confidence: 99%
See 3 more Smart Citations